Patterns of extra-territorial nest-box visits in a songbird suggest a role in extrapair mating. (23rd December 2022) - Santema, Peter; Kempenaers, Bart
Abstract: Many animals make visits outside of their territory during the breeding period, but these are typically infrequent and difficult to observe. As a consequence, comprehensive data on extra-territorial movements at the population-level are scarce and the function of this behavior remains poorly understood. Using an automated nest-box visit tracking system in a wild blue tit population over six breeding seasons, we recorded all extra-territorial nest-box visits ( n = 22 137) related to 1195 individual breeding attempts (761 unique individuals). Sixty-two percent of breeders made at least one extra-territorial visit between the onset of nest building and the day of fledging of their offspring, and individuals visited another nest-box on average on 11% of the days during this period. Visit behavior differed clearly between the sexes, with males making over three times as many extra-territorial forays as females. There was a strong overall seasonal decline in visit behavior, but this was sex dependent, with females showing a strong reduction in the number of extra-territorial visits before the onset of egg laying and males showing a strong and sudden reduction on the day their offspring hatched. The likelihood of visiting a particular nest-box declined sharply with the distance to that box, and blue tits almost exclusively visited direct neighbors. Individuals were more likely to have extrapair offspring with an individual whose box they visited, but they were not more likely to disperse to a box they had visited. Thus, our results are inconsistent with the hypothesis that extra-territorial nest-box visits serve to inform dispersal decisions, but suggest that such visits are linked to extrapair mating opportunities. Abstract : In blue tits, visits to nest-boxes outside a bird's territory vary in time and space, and suggest a potential role in extra-pair mating. We used an automated monitoring system to record all extra-territorial nest-box visits by birds over six breeding seasons. Visits were primarily performed by males, mainly took place during the early breeding period, and were restricted to close neighbors. Extra-territorial box visits predicted patterns of extra-pair paternity, but not patterns of breeding dispersal.